ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN POPUP BOOK PADA PELAJARAN IPS SISWA KELAS VI SD - Istiqomahh; Wawan Shokib Rondli; Agus Darmuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the needs of social studies learning media on the characteristics of ASEAN countries for grade VI elementary school students, especially at SD 8 Tanjungrejo and as a guide for teachers to create 3D-based social studies learning media, namely Pop Up Book to attract student interest in learning. The problem found by the teacher is that students have difficulty understanding ASEAN material, in the learning process the teacher only uses thematic books without any learning media to support understanding of the material. This research uses R&D (Research and Development) development research by referring to the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluation). This research is only limited to the analysis stage. The instrument used to collect data was a questionnaire. The data analysis technique is descriptive qualitative. This research data collection used interview techniques and the distribution of needs analysis questionnaires. The research was conducted in March 2024. Based on the results of the analysis conducted, it was found that 95% of students really need learning media as a companion to thematic books. And in further research it is hoped that learning media for social studies subjects on ASEAN material can be developed through 3D media in the form of pop up books.